2011
DOI: 10.1097/mpg.0b013e3181efe551
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Hyperactivity Results in Frequent Fecal Soiling in a Subset of Children After Surgery for Hirschsprung Disease

Abstract: Daily, frequent fecal soiling after pull-through surgery for HSCR may be due to colonic hyperactivity in some children. It is imperative that this unique subset be identified because the management strategy would include avoidance of laxatives, contrary to standard current practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 15 publications
(27 reference statements)
1
56
0
2
Order By: Relevance
“…We believe that this approach can be temporary in otherwise healthy patients, as it may allow recovery of the colonic dysfunction and eventually discontinue its use, although this has not been studied. The colon manometry has been reported as useful in clinical practice to typify the colonic physiology in defecations disorders in patients with colorectal disorders like Hirschsprung's disease 8,9 and imperforate anus, 10 to predict ACE outcome 11 and to guide surgical therapy in refractory constipation. 12,13 However, the diagnostic value of the CM to predict outcomes has not been properly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this approach can be temporary in otherwise healthy patients, as it may allow recovery of the colonic dysfunction and eventually discontinue its use, although this has not been studied. The colon manometry has been reported as useful in clinical practice to typify the colonic physiology in defecations disorders in patients with colorectal disorders like Hirschsprung's disease 8,9 and imperforate anus, 10 to predict ACE outcome 11 and to guide surgical therapy in refractory constipation. 12,13 However, the diagnostic value of the CM to predict outcomes has not been properly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies established that patients with Hirschsprung’s Disease have increased frequency of HAPCs after surgery compared to children without surgery 34 . The mechanism for this increase is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Colonic manometry in combination with ARM has emerged as an important tool in understanding the pathophysiology and guiding the management of persistent postoperative symptoms of patients with Hirschsprung's disease and anorectal malformations, such as imperforate anus. Treatment guided by the CM (laxatives when HAPCs were weak or absent and medications to increase stool consistency in the presence of HAPCs migrating to rectum with normal or low tone anal sphincter) resulted in a significant improvement in quality of life and frequency and consistency of bowel movements . It has been reported that 80% of patients with imperforate anus and fecal incontinence have HAPCs propagating into the neorectum and 60% have low internal anal sphincter resting pressure.…”
Section: Indicationsmentioning
confidence: 99%
“…To evaluate persistent symptoms following surgery, specifically for HAPCs were weak or absent and medications to increase stool consistency in the presence of HAPCs migrating to rectum with normal or low tone anal sphincter) resulted in a significant improvement in quality of life and frequency and consistency of bowel movements. 53,54 It has been reported that 80% of patients with imperforate anus and fecal incontinence have HAPCs propagating into the neorectum and 60% have low internal anal sphincter resting pressure. Treatment based on those findings resulted on improvement of fecal incontinence in 45% of patients.…”
mentioning
confidence: 99%